Clinical impact of whole-genome sequencing in patients with early-onset dementia. Issue 11 (29th July 2022) - Huq, Aamira J; Thompson, Bryony; Bennett, Mark F; Bournazos, Adam; Bommireddipalli, Shobhana; Gorelik, Alexandra; Schultz, Joshua; Sexton, Adrienne; Purvis, Rebecca; West, Kirsty; Cotter, Megan; Valente, Giulia; et al.
Abstract : Background: In the clinical setting, identification of the genetic cause in patients with early-onset dementia (EOD) is challenging due to multiple types of genetic tests required to arrive at a diagnosis. Whole-genome sequencing (WGS) has the potential to serve as a single diagnostic platform, due to its superior ability to detect common, rare and structural genetic variation. Methods: WGS analysis was performed in 50 patients with EOD. Point mutations, small insertions/deletions, as well as structural variants (SVs) and short tandem repeats (STRs), were analysed. An Alzheimer's disease (AD)-related polygenic risk score (PRS) was calculated in patients with AD. Results: Clinical genetic diagnosis was achieved in 7 of 50 (14%) of the patients, with a further 8 patients (16%) found to have established risk factors which may have contributed to their EOD. Two pathogenic variants were identified through SV analysis. No expanded STRs were found in this study cohort, but a blinded analysis with a positive control identified a C9orf72 expansion accurately. Approximately 37% (7 of 19) of patients with AD had a PRS equivalent to >90th percentile risk. Discussion: WGS acts as a single genetic test to identify different types of clinically relevant genetic variations in patients with EOD. WGS, if used as a first-line clinical diagnostic test, has the potential to increase the diagnostic yield and reduce time to diagnosis for EOD.